2009
DOI: 10.1177/155005940904000210
|View full text |Cite
|
Sign up to set email alerts
|

Recent EEG and ERP Findings in Substance Abusers

Abstract: Research on electroencephalographic (EEG) correlates of substance use has a long history. The present paper provides a review of recent studies -2001 to the present -with a focus on EEG findings in human participants characterized by a history of chronic substance use, abuse or dependence. In some areas (e.g., alcohol and cocaine dependence), the field has attempted to build upon earlier work by incorporating different methodologies or pursuing research questions of a transdisciplinary nature. New areas of inq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Although not definitive, this contrast in findings between their studies may indicate that while the LPC shows an altered response for chronic exposure measured during the unintoxicated state in comparison to acute exposure among casual users, N400 is less reliable in its expression following acute intoxication. It has recently been demonstrated that heavy chronic users of cannabis show evidence of reduced response and neuroadaptation to THC compared to occasional users (e.g., Ramaekers et al 2009 Ceballos et al (2009) has indicated both a high likelihood of neurophysiological disruption from chronic use as well as a distinct need to examine this further. The concordance of our control participant SME morphology with the findings of earlier investigations into this electrical complex (for review, see Friedman and Johnson 2000) implicates the expression of parahippocampal and hippocampal functioning in our results; as these are believed to be the generators of the SME N4 and LPC, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Although not definitive, this contrast in findings between their studies may indicate that while the LPC shows an altered response for chronic exposure measured during the unintoxicated state in comparison to acute exposure among casual users, N400 is less reliable in its expression following acute intoxication. It has recently been demonstrated that heavy chronic users of cannabis show evidence of reduced response and neuroadaptation to THC compared to occasional users (e.g., Ramaekers et al 2009 Ceballos et al (2009) has indicated both a high likelihood of neurophysiological disruption from chronic use as well as a distinct need to examine this further. The concordance of our control participant SME morphology with the findings of earlier investigations into this electrical complex (for review, see Friedman and Johnson 2000) implicates the expression of parahippocampal and hippocampal functioning in our results; as these are believed to be the generators of the SME N4 and LPC, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Event-related potentials (ERPs) are noninvasive markers of cortical activity that have been extensively used to delineate the neural correlates of alcoholism (10,11). It has been repeatedly demonstrated that alcoholics (and those at genetic risk for the disorder) exhibit attenuations of the P3(00) component (10).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive deficits in alcohol dependent subjects have been described extensively, and can vary from severe memory problems as observed in Korsakoff’s syndrome to subtle deficits observed in the processing of a stimulus, as seen in decreased P3 amplitude (Ceballos et al, 2009; Oscar-Berman and Zola-Morgan, 1980; Oscar-Berman et al, 1982; Porjesz and Begleiter, 2003; Porjesz et al, 2005; Tarter and Ryan, 1983). Electrophysiological studies of adult alcoholics and high risk children of alcoholics have found alterations generally in N1, N2, P2 and P3, where only the reduced P3 amplitude was a robust finding across laboratories and across experimental paradigms (Cohen et al, 1997; Fein and Chang, 2006; Kamarajan et al, 2005a; Miyazato and Ogura, 1993; Oscar-Berman, 1987; Pfefferbaum et al, 1991; Porjesz and Begleiter, 1985; Porjesz and Begleiter, 1987; Prabhu et al, 2001; Realmuto et al, 1993; Rodriguez Holguin et al, 1998; Rodriguez Holguin et al, 1999a; Rodriguez Holguin et al, 1999b; Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%